2022
DOI: 10.1097/aog.0000000000004841
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Surgeon Self-Reflection on Hysterectomy Quality Metrics

Abstract: Self-reflection of attending gynecologic surgeons on hysterectomy complication rate is inaccurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This requires surgeons to be aware of their complication rates, and yet a recent quality study showed that gynecologists significantly underestimate their complication rates, with fellowship-trained surgeons doing the worst. 9 Clearly, there is room for improvement in patient counseling and shared decision making.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This requires surgeons to be aware of their complication rates, and yet a recent quality study showed that gynecologists significantly underestimate their complication rates, with fellowship-trained surgeons doing the worst. 9 Clearly, there is room for improvement in patient counseling and shared decision making.…”
mentioning
confidence: 99%
“…The nature of our specialty, with a focus on issues that affect quality of life, highlights shared decision making that balances both efficacy and risks of interventions as imperative for achieving patient-centered care. This requires surgeons to be aware of their complication rates, and yet a recent quality study showed that gynecologists significantly underestimate their complication rates, with fellowship-trained surgeons doing the worst 9 . Clearly, there is room for improvement in patient counseling and shared decision making.…”
mentioning
confidence: 99%